2023
DOI: 10.1002/anie.202219153
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Oxygen Dilemma in Photoredox Catalysis: Near‐Infrared (NIR) Light‐Triggered Peroxynitrite Generation for Antibacterial Applications

Abstract: The peroxynitrite anion (ONOO−) is closely associated with many diseases and the creation of ONOO− donors is an essential means of understanding its pathophysiological functions. However, it is challenging to develop ONOO− donors due to the difficulties in simultaneously producing highly reactive and short‐lived nitric oxide (NO) and superoxide anion (O2⋅−). Here, we report a novel strategy for constructing ONOO− donors by combining near‐infrared (NIR)‐mediated type I photosensitization and photoredox catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…[44] Based on the above results and literature reports of NO release through photoredox catalysis, [10,44] a plausible mechanism is shown in , which finally expected to be readily in situ transformed to MeNH-H 2 BDC in aqueous solutions. [10,45,46,47] Facilitating NO release via PET process is a novel approach and a similar mechanism have been documented by Hu et al, who enabled the NO release of coumarin-based NO donors under red-light irradiation (up to 700 nm) activated by palladium(II) tetraphenyltetrabenzoporphyrin derivatives through the PET process. [45] As shown in Figure S21 (Supporting Information), the PTIO signal gradually decreases under UV irradiation (365 nm), and the EPR signal of NNO@MIL-88B weaken faster than that of MeNNO-H 2 BDC under the same irradiation conditions, which indeed confirmed that the PET process can accelerate the NO release.…”
Section: Study On No-releasing Mechanismmentioning
confidence: 63%
See 1 more Smart Citation
“…[44] Based on the above results and literature reports of NO release through photoredox catalysis, [10,44] a plausible mechanism is shown in , which finally expected to be readily in situ transformed to MeNH-H 2 BDC in aqueous solutions. [10,45,46,47] Facilitating NO release via PET process is a novel approach and a similar mechanism have been documented by Hu et al, who enabled the NO release of coumarin-based NO donors under red-light irradiation (up to 700 nm) activated by palladium(II) tetraphenyltetrabenzoporphyrin derivatives through the PET process. [45] As shown in Figure S21 (Supporting Information), the PTIO signal gradually decreases under UV irradiation (365 nm), and the EPR signal of NNO@MIL-88B weaken faster than that of MeNNO-H 2 BDC under the same irradiation conditions, which indeed confirmed that the PET process can accelerate the NO release.…”
Section: Study On No-releasing Mechanismmentioning
confidence: 63%
“…The resultant [MeN‐H 2 BDC] − anions can further reduce [Fe 3 ─O] •+ moieties to recover [Fe 3 ─O] with the generation of [MeN‐H 2 BDC] • , which finally expected to be readily in situ transformed to MeNH‐H 2 BDC in aqueous solutions. [ 10,45,46,47 ] Facilitating NO release via PET process is a novel approach and a similar mechanism have been documented by Hu et al., who enabled the NO release of coumarin‐based NO donors under red‐light irradiation (up to 700 nm) activated by palladium(II) tetraphenyltetrabenzoporphyrin derivatives through the PET process. [ 45 ]…”
Section: Resultsmentioning
confidence: 81%
“…Nile blue analogs are non‐metal organic molecules that can serve as both Type I photosensitizers and metal‐free photocatalysts, generating O 2 ⋅ − and NO simultaneously when excited by near‐infrared light, further producing peroxynitrite anions, displaying good antibacterial and anti‐biofilm functions (Figure 1d). [21] …”
Section: Photocatalytic Release Of Gasotransmittersmentioning
confidence: 99%
“…In addition to inferring the concentration of released NO, the ratiometric analysis of the fluorescence signal from these fluorogenic NO donor vehicles also implicated the in vitro distribution of NO, which aids in the understanding of their pharmacodynamics. To date, a few UV and visible light triggered NO-releasing N -nitrosamine based polymers have been reported to execute this specific purpose. Therefore, development of a fluorogenic water-soluble polymeric NO donor to maintain the hydrophilic and hydrophobic balance would aid in fabricating a versatile drug delivery system. Thus, a water-soluble polymeric NO donor is designed to exhibit micelle-forming ability with a fluorogenic response upon NO release.…”
Section: Introductionmentioning
confidence: 99%